2021
DOI: 10.3389/fphar.2021.746910
|View full text |Cite
|
Sign up to set email alerts
|

Spermine-Related DNA Hypermethylation and Elevated Expression of Genes for Collagen Formation are Susceptible Factors for Chemotherapy-Induced Hand-Foot Syndrome in Chinese Colorectal Cancer Patients

Abstract: Hand-foot syndrome (HFS) is a common capecitabine-based chemotherapy-related adverse event (CRAE) in patients with colorectal cancer (CRC). It is of great significance to comprehensively identify susceptible factors for HFS, and further to elucidate the biomolecular mechanism of HFS susceptibility. We performed an untargeted multi-omics analysis integrating DNA methylation, transcriptome, and metabolome data of 63 Chinese CRC patients who had complete CRAE records during capecitabine-based chemotherapy. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“… 36 Furthermore, our recent study showed that HFS-related transcriptome changes of normal colorectal tissue had an overall suppressed inflammation profile. 7 Our food/nutritional findings are also in accordance with the well-established function of milk in anti-inflammation. The fat content and fermentation effect do not affect the anti-inflammation effect.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“… 36 Furthermore, our recent study showed that HFS-related transcriptome changes of normal colorectal tissue had an overall suppressed inflammation profile. 7 Our food/nutritional findings are also in accordance with the well-established function of milk in anti-inflammation. The fat content and fermentation effect do not affect the anti-inflammation effect.…”
Section: Discussionsupporting
confidence: 86%
“…The plasma metabolome data of the 36 patients was acquired from published data. 7 To put it briefly, an UHPLC system coupled to a quadruple time-of-flight mass spectrometer was utilized for the metabolome assays. All the samples were screened separately under both positive and negative ionization modes, and the detailed methods of data pre-processing about metabolome were described in our previous study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not least, screening miRNAs from normal tissues other than tumors may provide more informative clues. Accumulating evidence suggests that the efficacy and safety of chemotherapy are not solely dependent on drug metabolism but also on the overall physiological functions [44,[48][49][50][51][52][53]. Individual differences in cell maintenance, proliferation, and immune function also influence the response to chemotherapy.…”
mentioning
confidence: 99%